Faktor Persepsi dan Keputusan Wisatawan Berkunjung Kembali ke Kawasan Malioboro Yogyakarta: Pendekatan Psikologi Lingkungan - Adin, Dheanisa Miftahul; Aulia, Riefda Faizatul; Kuncoro, Muhammad Jati (Fakultas Teknik - Universitas Bung Karno, 2024)
Malioboro area of ​​Yogyakarta is one of the popular recreational place in the form of a pedestrian street in Indonesia. The popularity of Malioboro itself cannot be separated from the status of the city of Yogyakarta itself as a tourist, cultural and educational city. From a psychological aspect, residents' perceptions place Malioboro as an attractive area to visit for various tourist activities. Knowledge about attractions and decisions is interesting to know in developing tourist areas in Indonesia, especially from a behavioral architecture perspective. This research aims to determine the psychological factors in tourists' decisions to visit again. The assumption is that there is an influence on the positive experiences of tourists during their visit. This research question is how psychological aspects influence visitors' perceptions of returning visits. The research method used is descriptive qualitative by observing existing visitor activities related to their positive experiences. There are 3 groups of observations, namely: spatial cognition phenomena, spatial behavior and spatial order. The results of this research show that spatial cognition is the most influential factor in making this area's place attractive to visit.